2011 Design, Automation &Amp; Test in Europe 2011
DOI: 10.1109/date.2011.5763086
|View full text |Cite
|
Sign up to set email alerts
|

Run-time deadlock detection in networks-on-chip using coupled transitive closure networks

Abstract: Interconnection networks with adaptive routing are susceptible to deadlock, which could lead to performance degradation or system failure. Detecting deadlocks at run-time is challenging because of their highly distributed characteristics. In this paper, we present a deadlock detection method that utilizes run-time Transitive Closure (TC) computation to discover the existence of deadlock-equivalence sets, which imply loops of requests in networks-on-chip (NoC). This detection scheme guarantees the discovery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Moreover, it has been shown that even in a data network, deadlock is a very rare and detectable event [41], so that unrestricting the routing by allowing any turn is recommended. The rareness of deadlock is emphasized in SHiFA as the control packets are (i) rarely generated and (ii) mainly transferred in local distances.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that even in a data network, deadlock is a very rare and detectable event [41], so that unrestricting the routing by allowing any turn is recommended. The rareness of deadlock is emphasized in SHiFA as the control packets are (i) rarely generated and (ii) mainly transferred in local distances.…”
Section: Discussionmentioning
confidence: 99%